2014
DOI: 10.3171/2014.7.jns14236
|View full text |Cite
|
Sign up to set email alerts
|

Reducing costs while maintaining quality in endovascular neurosurgical procedures

Abstract: W ith health care reform headlining the media, both the US government and its citizens are acutely aware that funding medical care will continue to be a challenging problem as we face limited supplies and increasing demand. To this end, the cost-effectiveness of managing aneurysms using various endovascular techniques versus open microsurgical management has been much debated. Endovascular treatments are usually considered more costly, especially up-front procedures that include the use of expensive radiology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 6 publications
0
7
0
2
Order By: Relevance
“…Gandhoke and colleagues 5 developed a capped-price model and showed that with capitation of endovascular materials, substantial budget control on supply costs can be achieved. Kashlan et al 8 reported significant budget saving with endovascular interventions when economical contrast media and standardized coil pricing were employed and when medical waste was reduced. Our institution utilizes a neurovascular price-control committee in which these issues are discussed and negotiated with vendors.…”
Section: Cost-containment Strategiesmentioning
confidence: 99%
“…Gandhoke and colleagues 5 developed a capped-price model and showed that with capitation of endovascular materials, substantial budget control on supply costs can be achieved. Kashlan et al 8 reported significant budget saving with endovascular interventions when economical contrast media and standardized coil pricing were employed and when medical waste was reduced. Our institution utilizes a neurovascular price-control committee in which these issues are discussed and negotiated with vendors.…”
Section: Cost-containment Strategiesmentioning
confidence: 99%
“…When surgeons are given information on procedural and equipment costs, cost savings are realized in response to that feedback. 14,15) The growing interest in the cost of expendable surgical items, number of instruments used, efforts toward efficient use of purchased equipment, and improving technology and endoscopic surgical procedure experience, should further reduce costs. However, the length of hospitalization is short due to the minimally invasive nature of FELD, and will yield no obvious benefits to the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Kashlan et al 1 reported on an estimated cost savings of $76,732 after implementing a standardized coil price, calculated by dividing the total cost of all coils used in each 6-month period by the number of coils used. As an example, they state, "Coil A, which may cost $200 from Vendor 1, $400 from Vendor 2, $1000 from Vendor 3, and $800 from Vendor 4, would have an average shelf price of $600."…”
Section: Discussionmentioning
confidence: 99%